Pengaruh Literasi Keuangan, Gaya Hidup, Kontrol Diri Terhadap Perilaku Konsumtif Mahasiswa (Studi Pada Mahasiswa Universitas Islam Malang) - Miranda Aulia Udayani; Muhammad Agus Salim; Ita Athia (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The purpose of this study is to investigate and explain the impact of financial literacy, lifestyle, and self-control on the consumption behavior of Islamic University of Malang students in the class of 2019. As many as 100 responders successfully gathered the available samples. Although SPSS is utilized for analysis, Multiple Linear Regression is employed. According to the findings of this study, financial literacy, lifestyle, and self-control all have a simultaneous influence on consumption, and financial literacy and lifestyle have a large positive effect on consumption while self-control has a considerable negative effect. Keywords : Financial Literacy, Lifestyle, Self-Control.